MicroRNAs as biomarkers for clinical studies - Pogribny, Igor P (Exp Biol Med (Maywood), 2017)
The development of better diagnostic and prognostic non-invasive biomarkers holds an enormous potential to improve the ability to diagnose and individualize treatment of a great number of human diseases and substantially reduce health care cost. The discovery of a fundamental role of microRNAs in the disease pathogenesis and their presence and stability in biological fluids has led to extensive investigation of the role of microRNAs as potential non-invasive biomarkers for disease diagnosis and prognosis. The result of this research has suggested that alterations of microRNAs may be sensitive indicators of various pathologies; however, despite the indisputable progress in this field, the diagnostic promise of microRNAs has remained a work in progress, and circulating microRNAs have not entered the field of clinical medicine yet. Commonly reported microRNAs as disease biomarkers are largely not disease-specific and the results are often contradicting in independent studies. This review summarizes the current knowledge on the role of microRNAs as disease indicators and emphasizes the current gaps, challenges, and questions that need to be addressed in future well-designed and well-controlled studies for a successful translation of microRNA profiling into clinically meaningful tests. IMPACT STATEMENT: This review summarizes the current knowledge on the role of circulating miRNAs as clinical diagnostic biomarkers and highlights the challenges that need to be addressed in future studies for a successful translation of circulating miRNAs into a novel diagnostic tool.